Pengaruh Kemampuan Berpikir Kritis Siswa Terhadap Hasil Belajar Matematika - Queena Alzena; Rais Hidayat; Rukmini Handayani (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2023)
The purpose of this study was to determine the effect of students' critical thinking skills on mathematics learning outcomes. This study uses a quantitative method with a causal approach. The research subjects were fifth grade students of SDN Karadenan with a sample of 47 students from 90 students obtained using the Taro Yamane formula. This research was conducted in the odd semester of the 2022/2023 academic year. Testing prerequisite analysis in the form of the Liliefors test and Fisher's exact test. The results showed that there was an influence between Critical Thinking Ability (X) on Mathematics Learning Outcomes (Y) statistically proven by the results of the significance test and the regression equation = - 14,4 + (0,98X). This means that for every one unit increase in the critical thinking ability variable, student learning outcomes will also increase by 0.98 units. The strength between Critical Thinking Ability (X) on Mathematics Learning Outcomes (Y) is evidenced by a correlation coefficient of (rxy) 0,97 with a determination coefficient of 0,9467. This shows that there is a significant positive influence between students' critical thinking skills on mathematics learning outcomes.